OPTIMIZATION AND CHARACTERIZATION OF CHITOSAN-BASED NANOPARTICLES CONTAINING METHYLPREDNISOLONE USING BOX-BEHNKEN DESIGN FOR THE TREATMENT OF CROHN’S DISEASE - SHARMA, GANESH N.; KUMAR, C. H. PRAVEEN; SHRIVASTAVA, BIRENDRA; KUMAR, B. (International Journal of Applied Pharmaceutics, 2020)
Objective: The present research was designed to produce methylprednisolone containing chitosan-based nanoparticles using Box-Behnken Design (BBD) and Response Surface Methodology (RSM) for optimization. Methods: Nanostructures were prepared using the ionic gelation method with screened process parameters. According to the design, methylprednisolone chitosan-based nanoparticles (MCSNPs) were optimized using factors like methylprednisolone concentration, stirring speed and temperature whereas particle size, zeta potential and % encapsulation efficiency as responses. From the observed values of responses with confirmation location and desirability, the predicted values were very close to the observed values. Results: Observed values for the optimized formulation have a particle size of 243±2.33 nm with an encapsulation efficiency of 79.3±7.2%. Morphology of the particles using scanning electron microscopy reveals nearly spherical shaped particles. Methylprednisolone was released in vitro in a sustained manner for about 24 h in simulated colonic fluid pH 7, pH 7.8 (Fasted state) and phosphate buffer pH 7.4, when compared to simulated colonic fluid at pH 6 (Fed state). Optimized MCSNPs followed Korsmeyer peppas kinetics with drug release mechanism as anomalous transport. Conclusion: Application of Box-Behnken design and Response Surface Methodology using Design Expert software was successfully used in the optimization of methylprednisolone loaded chitosan-based nanoparticles with high encapsulation efficiency.